The Impact of Digitalization on the Creative Economy Chain Management Strategy and the Halal Industry in the Sambal Ambruk MSME in Darmayasa Village, Pejawaran, Banjarnegara - M. Fathrezza Imani; Muhammad Ghoitsun Nada; M. Rizky Andrean (Yayasan Abdurrauf Cendekia Nusantara, 2026)
Product sales by MSMEs in Indonesia often encounter obstacles due to a lack of digital literacy in their management, including those faced by the Sambal Ambruk MSME. This study aims to help address the root causes of the implementation of digitalization and Sharia economic principles in the management of the Sambal Ambruk MSME using a qualitative descriptive method with a case study approach through observation, interviews, and documentation. Informants were selected based on their roles directly related to the business management process: Mr. Tumar (Head of Darmayasa Village), Ms. Haryanti (Member of the Darmayasa Village Youth Organization), Ms. Turiyah (Middleman and Farmer in Darmayasa Village), and Ms. Eni Khayatun (Activist and resident of Darmayasa Village). The study found that the Sambal Ambruk MSME, located in Darmayasa Village, Pejawaran District, Banjarnegara Regency, has implemented Sharia economic principles and digitalization within its premises. The implementation of this program offers numerous benefits, including: operational efficiency, increased market access and wider consumer reach, reduced promotional costs, increased profits, more attractive packaging, and the display of product identity and characteristics, thus distinguishing MSMEs from competitors. However, contributions from various parties are needed to develop the Creative Economy in Darmayasa Village, including the Village Government, Youth Organization members, middlemen, farmers, and villagers themselves, so that Sambal Ambruk can remain competitive and become a unique attraction amidst today's digital economy. [Penjualan produk pada UMKM di Indonesia kerap mengalami kendala dikarenakan kurangnya literasi akan Digitalisasi pada pengelolaannya, termasuk yang dihadapi oleh UMKM Sambal Ambruk. Penelitian ini bertujuan untuk membantu penyelesaian akar masalah akan implementasi Digitalisasi dan pronsip Ekonomi Syariah terhadap manajemen dan pengelolan UMKM Sambal Ambruk dengan metode deskriptif kualitatif dengan pendekatan Studi Kasus melalui observasi, wawancara dan dokumentasi. Informan ditentukan berdasarkan peran yang berhubungan langsung dengan proses pengelolaan usaha, yaitu Bapak Tumar (Kepala Desa Darmayasa), Ibu Haryanti (Anggota Karang Taruna Desa Darmayasa), Ibu Turiyah (Tengkulak dan Petani Desa Darmayasa), Ibu Eni Khayatun (Aktivis dan warga Desa Darmayasa). Hasil penelitian menyatakan bahwa UMKM Sambal Ambruk terletak di desa Darmayasa, Kecamatan Pejawaran, Kabupaten Banjarnegara, dan telah menerapkan prinsip ekonomi Syariah serta implementasi Digitalisasi dialamnya. Banyak sekali manfaat yang didapatkan dengan penerapan tersebut, diantaranya : Efisiensi kegiatan operasional, Peningkatan akes pasar dan konsumen yang lebih luas, Penekanan biaya promosi yang lebih rendah, Keuntungan semakin meningkat, Pengemasan semakin menarik serta Menampilkan identitas dan ciri khas produk sehingga membedakan produk UMKM dari pesaing. Namun perlu adanya kontribusi dari berbagai pihak akan pengembangan Ekonomi Kreatif yang ada di desa Darmayasa seperti peran dari Pemerintah Desa, Anggota Karang Taruna, Tengkulak dan para Petani serta warga desa sendiri agar Sambal Ambruk tetap eksis dan tidak kalah saing serta menjadi daya tarik tersendiri ditengah perkembangan ekonomi digital saat ini.]